The Association Between Gastroesophageal Reflux Disease (Gerd) And Sleep Quality Among Medical Students of The Indonesian Muslim University Class of 2021 - Moh. Hamdhan Hamsa; Indah Lestari Daeng Kanang; Hanna Aulia Namirah; Darariani Iskandar; Ilma Khaerina Amaliyah Bakhtiar (CV. Inara, 2025)
The Association Between Gastroesophageal Reflux Disease (Gerd) and Sleep Quality in Medical Faculty Students of Indonesian Muslim University Class of 2021. Gastroesophageal Reflux Disease (GERD) is a chronic gastrointestinal disorder characterized by the regurgitation of stomach contents into the esophagus, causing symptoms such as heartburn, regurgitation, sore throat, and cough. GERD can worsen sleep quality, contributing to sleep disorders. This study aims to examine the association between GERD and sleep quality among medical students at Indonesian Muslim University Class of 2021. This study emploved a descriptive analytics desing with a cross-sectional approach, and the sample was selected through total sampling. The chi-square test was applied to analyze the association between GERD and sleep quality with a significance level of p < 0.05. Among 274 respondents, 45 (16.4%) had GERD, while 229 (83.6%) did not. Additionally, 42 (15.3%) had good sleep quality, whereas 232 (84.7%) had poor sleep quality. Statistical analysis showed a p-value = 0.027, indicating a significant association between GERD and sleep quality (p < 0.05). The findings suggest that students with GERD are at a higher risk of experiencing poor sleep quality. These results highlight the need for preventive measures and interventions to improve sleep quality in students suffering from GERD.